1983
DOI: 10.1111/j.1600-0609.1983.tb01456.x
|View full text |Cite
|
Sign up to set email alerts
|

Folic Acid Deficiency in β‐Thalassaemia Heterozygotes

Abstract: Plasma and red cell folate mean contents have been found to be significantly lower in 41 symptom-free P-thalassaemia heterozygotes than in 21 controls. Such decreases must be considered as effects of an increased folate utilization caused by the enhanced total, both effective and ineffective, erythropoiesis. Since no close correlation has been found between packed cell volume and plasma or red blood cell folate levels, it seems that in 'healthy' P-thalassaemia subjects, the degree of anaemia is not influenced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Although these studies were small, both found an increased risk of NTDs overall among women with thalassemia compared with women without thalassemia. The mechanism by which HHA can lead to NTDs is unclear, but studies have shown that women with HHA may suffer from depleted folate reserves due to the decrease in healthy red blood cells (Castaldi et al, 1983; Dixit et al, 2016). These low folate reserves may explain our finding of increased risk of anencephaly among women with HHA, since low folic acid has been found to be associated with NTDs in numerous studies (Ibba et al, 2003; Williams et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Although these studies were small, both found an increased risk of NTDs overall among women with thalassemia compared with women without thalassemia. The mechanism by which HHA can lead to NTDs is unclear, but studies have shown that women with HHA may suffer from depleted folate reserves due to the decrease in healthy red blood cells (Castaldi et al, 1983; Dixit et al, 2016). These low folate reserves may explain our finding of increased risk of anencephaly among women with HHA, since low folic acid has been found to be associated with NTDs in numerous studies (Ibba et al, 2003; Williams et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…It is an effect of increased folate utilization caused by the enhanced total, both effective and ineffective erythropoiesis, further contributing to the change in RBC morphology. [11] Thus, the varied morphologies seen in multi-transfused patients are not only attributable to thalassemia, but a wide variety of causes. As explained above, target cells can indicate underlying liver disease and normocytic hypochromic erythrocytes may be because of underlying folate deficiency and/or liver disease.…”
Section: Discussionmentioning
confidence: 99%